(3GdVjGA GddGeY TQM LeY GdLhGeYs - (3LdGd GdOjf eMeO Hf CMeO GdeMdi GdTGaYjs; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s
(3ChdgG (B:s
(3HGdCUd aEfg Od Odjd Ydi hLhH CNP Hg ceG ai ZSdGJ hdhZ GdcdH s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf hHg Je GdVjGA GddGeY TQM LeY GdLhGeY ddTjN GdEeGe LdGd GdOjf CHj YHO Gddg eMeO Hf GdTjN TgGH GdOjf CMeO GdeMdi GdTGaYi hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bWYI efgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
Keywords: (3Gdabg GdTGaYjs